'We Will End Up Being a Third Rate Economy … A Banana Republic': How Behavioural Economics Can Improve Macroeconomic Outcomes. (June 2017) - McDonald, Ian M.
Abstract: To address the economic problems facing Australia in 1986 required wage restraint, which required in turn overcoming loss aversion by workers with respect to their wages. The Prices and Incomes Accord was able to do this. Attempts to address Australia's current economic problems are stymied by tax resistance. Addressing tax resistance requires overcoming loss aversion by voters with respect to their post‐tax incomes. The success of the Accord suggests that Accord‐type policies could reduce tax resistance by broadening people's perspective beyond their post‐tax incomes to the broader spread of benefits for them and others .